PENGARUH UKURAN PERUSAHAAN,OPERATING LEVERAGE, DAN PERINGKAT OBLIGASI TERHADAP PERATAAN LABA PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Astari Nadia (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2014)
The purpose of this research is to examine the factors that impact income smoothing in Indonesia. The issues investigated in this research were factors such as company size, operating leverage,and the bond ratings. The data are collected from 24 listed companies in Indonesian Stocks Exchange (ISX). Selection process were using (purposive) sampling method. The sampling companies then classified into smoother and non smoother using Eckel’s model. The result shows that there are some companies listed in Indonesian Stocks Exchange that practice income smoothing. Data analysis worked by using Descriptive Statistic,Hosmer and Lemeshow test, Omnibus tests of model coefficients, Nagelkerke’s R Square, and Logistic Regression. Based on statistic test, the result show that the bond ratings influence on income smoothing. As for company size and operating leverage have no influence on income smoothing.